2019
DOI: 10.1021/jacs.9b00241
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Formycin A Biosynthetic Gene Cluster from Streptomyces kaniharaensis Illustrates the Interplay between Biological Pyrazolopyrimidine Formation and de Novo Purine Biosynthesis

Abstract: Formycin A is a potent purine nucleoside antibiotic with a C-glycosidic linkage between the ribosyl moiety and the pyrazolopyrimidine base. Herein, a cosmid is identified from the Streptomyces kaniharaensis genome library that contains the for gene cluster responsible for the biosynthesis of formycin. Subsequent gene deletion experiments and in vitro characterization of the forBCH gene products established their catalytic functions in formycin biosynthesis. Results also demonstrated that PurH from de novo puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 38 publications
5
52
0
Order By: Relevance
“…2A, Tables 1, S1). As anticipated, in silico analysis indicated that the genes for FOR-A and COF biosynthesis are linked together as reported by a recent study (19). Moreover, there are 7 additional genes ( forW, forV, forO, forG, cof25, cof26 , and cof29 ) in S. kaniharaensis ATCC 21070 (Table S1), and it is proposed to execute some alternative functions during FOR-A and COF biosynthesis in this strain.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…2A, Tables 1, S1). As anticipated, in silico analysis indicated that the genes for FOR-A and COF biosynthesis are linked together as reported by a recent study (19). Moreover, there are 7 additional genes ( forW, forV, forO, forG, cof25, cof26 , and cof29 ) in S. kaniharaensis ATCC 21070 (Table S1), and it is proposed to execute some alternative functions during FOR-A and COF biosynthesis in this strain.…”
Section: Resultssupporting
confidence: 83%
“…6A), and related biochemical studies in our laboratory are now ongoing. Once the C -glycosidic bond constructed, the later tailoring enzymatic steps are highly similar to those in the de novo purine pathway, which has already been illustrated in two recent studies (19, 26).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This gene cluster contains af our-gene subcluster (pyrOPQS)t hat has been linked to the biosynthesis of coformycin,t he production of which seems to be associated with many nucleoside family natural products (Figure S1 A). [18,19] Moreover, the pyr cluster also contains pyrE,w hich shows sequence homology to genes that encode( b-ribofuranosylamino)benzene 5'-phosphate (b-RFAP) synthase. In the biosynthesis of methanopterin, b-RFAP synthase catalyzes the condensation of p-aminobenzoic acid with phosphoribosylpyrophosphate throughaC -glycosidic linkage.…”
mentioning
confidence: 99%
“…[7] We note that the pyr clusters hares many homologous genes with the recently reported formycinb iosynthetic gene cluster (for cluster). [19] In view of the great structural similarity between pyrazomycina nd formycin, it is not unexpected that they might use similarb iosynthetic genes. Ta ken together,o ur in silico analysis suggested that the pyr cluster might be responsible for PZN assembly in S. candidus NRRL 3601.…”
mentioning
confidence: 99%